Environmental ethics: duties to the ordinary world - Shweta Singh Singh (International Journal of Atmosphere, 2025)
Environmental justice is a crucial framework that ensures fair and equitable access to clean air, water, and natural resources for all, particularly for marginalized and vulnerable populations. It addresses the environmental inequalities and injustices that disproportionately impact ordinary people and communities. This research highlights the pressing need to bridge the gap between environmental protection and social equity, ensuring that no community bears an undue burden of environmental degradation while others reap the benefits.The paper advocates for practices of stewardship and conservation at individual, community, and societal levels. These practices include responsible management of natural resources, sustainable land use, habitat restoration, and conservation efforts aimed at preserving the ordinary elements of the natural world. It emphasizes the importance of protecting local environments, common resources, and everyday landscapes that form the backbone of human and ecological well-being. By safeguarding these elements, the study promotes a sustainable future and a healthier planet for generations to come.Central to the research is the concept of environmental ethics, which defines the moral responsibilities humans have toward the ordinary, often overlooked aspects of the natural world. "Environmental Ethics: Duties to the Ordinary World" argues that beyond grand gestures of conservation, everyday landscapes and resources demand equal attention and care. The paper underscores the value of local ecosystems and highlights how these are critical to maintaining the ecological balance and quality of life for all species.Additionally, the study calls for collective action to restore and protect ordinary natural elements. It emphasizes the interdependence between human well-being and environmental stewardship, advocating for policies and initiatives that prioritize conservation. By fostering environmental justice and ethical responsibility, the research urges societies to adopt sustainable practices that not only reduce disparities but also promote a balanced relationship with nature.Ultimately, this research offers a vision for a future where communities, individuals, and policymakers work collaboratively to protect and preserve the ordinary natural world, ensuring its continuity for present and future generations.
Keywords: Marginalized; Vulnerable; conservation; inequalities; resources; stewardship